CONCEPT OF HOME: ISSUES OF ASSIMILATION, RACISM AND IDENTITY IN HOMEWARD: TOWARDS A POETICS OF SPACE - Jayalaxmi, Ph.; Singh, Elangbam Priyokumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The concept of home as a static space undergoes its meaning in modern times. Homelessness and displacement happen to be the apprehension of modern times. What is home to the Northeast people who are constantly displaced by violence? Embedded in this concept is the issue of belongingness, which, in the context of the people belonging to Northeast India, poses a problem of integrating into mainland India, which is drastically different in terms of culture, features, languages, food habits, etc. The question posits the reasons for (re)conceptualizing the concept of home among the Northeast people. The persistent discourse on Northeast India is defined through the perspective of this region’s dominant stereotype, which is reinforced through many discourses concerning conflict, displacement, violence, and so forth due to the troubled colonial past. This present paper foregrounds the understanding of the sense of belongingness, assimilation, identity, alienation and racism, eventually changing the perception of home. For this paper, selected pieces from Homeward: Towards a Poetic of Space will be analyzed to understand the polyphonic voices that emerged from the Northeast writers, giving different meanings to the notion of “home”.